Superspreaders: A Lurking Danger in the Community. (January 2021) - Mohindra, Ritin; Ghai, Arushi; Brar, Rinnie; Khandelwal, Neha; Biswal, Manisha; Suri, Vikas; Goyal, Kapil; Singh, Mini P.; Bhalla, Ashish; Rana, Kirtan; Lakshmi, P. V. M.
A "superspreader" refers to an unusually contagious organism infected with a disease. With respect to a human borne illnesses, a superspreader is someone who is more likely to infect other humans when compared to a typically infected person. The existence of human superspreaders is deeply entrenched in history; the most famous case being that of Typhoid Mary. Through contact tracing, epidemiologists have identified human superspreaders in measles, tuberculosis, rubella, monkeypox, smallpox, Ebola hemorrhagic fever, and SARS. The recent outbreak of Coronavirus disease (COVID-19) has shifted the focus back on the superspreaders. We herein present a case report of a COVID-19 superspreader with a hitherto unusually high number of infected contacts. The index case was a 33 year old male who resided in a low income settlement comprising of rehabilitated slum dwellers and worked as a healthcare worker (HCW) in a tertiary care hospital and had tested positive for COVID-19.On contact tracing, he had a total of 125 contacts, of which 49 COVID-19 infections had direct or indirect contact with the index case, qualifying him as a "superspreader." This propagated infection led to an outbreak in the community. Contact tracing, testing and isolation of such superspreaders from the other members of the community is essential to stop the spread of this disease and contain the COVID-19 pandemic.